Nikah Bawah Tangan Dan Itsbat Nikah - Abd. Basit Misbachul Fitri; In'am Fauzi; Abdul Wahid Azza (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
According to Law no. 1 of 1974, Marriage is a spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in God Almighty. Underhand marriage is a marriage that is carried out in secret without being attended by anyone except those who are getting married. In Indonesia it is called a sirri marriage, meaning veiled, closed, silent, private. This marriage is hidden from the public, and is not registered at the authorized institution. Marriage under the hand is legal according to religion only (if the conditions and pillars have been fulfilled), but does not get legal legality from the state. The Indonesian Ulema Council (MUI) in 1980 issued a fatwa: